New phraseological units with word soul (on the material of the social network «Instagram») - S. N. Glazkova; A. A. Rodina (Омский научный вестник: Серия "Общество. История. Современность")
The article considers a new linguistic phenomenon, widely spread in social networks — «hashtag». A plan of the expression and a plan of the content of hashtags are analyzed in social networks. It is concluded that the hashtag is an interesting object for linguistic research. The hashtags with the word «soul» and its synonyms in the social network «Instagram» are analyzed and grouped